Bondarenko Julia. The nature of the pronunciation standard-Еstuary English - Bondarenko Julia (Philological Treatises, 2020)
The nature of Estuary English is investigated in this paper. The description of phonemic variety of this pronunciation standard is analyzed. The Popularity of the Pronunciation Standard is given.